Adolescents’ Perceptions of Ghosts: A Phenomenological Study on the Influence of Culture and Digital Media - Nayla, Muthia Rahman; Suryanto (Philanthropy: Journal of Psychology, 2025)
Ghost stories are part of the culture that plays a role in shaping adolescents' understanding and perception of the immaterial world. However, culture and the role of digital media can also influence adolescents' understanding and perception. This study aims to determine the perception of ghosts in adolescents and understand the subjective experiences of late adolescents (aged 17–19 years) in forming these perceptions. This study employed a qualitative approach with a phenomenological method with Interpretative Phenomenological Analysis data analysis. Subjects were selected purposively. The data collection process involved in-depth interviews. The results of the study show that adolescents' perceptions of ghosts are complex and influenced by several factors, namely culture, social media, religion, social narratives, and individual experiences. These results indicate that understanding the dynamics of the formation of adolescents' perceptions of metaphysical phenomena in the digital era is very important. This has an impact on developmental and educational psychology, especially in helping adolescents understand and manage their emotions, imagination, and the way they think about supernatural stories.